MANAJEMEN PRODUKSI IKLAN BISNIS PADA RADIO MANDIRI FM 98.3 PEKANBARU - Setiabudi, Yanwar; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The continued development of technology , the radio is now an assortment of ease in establishing interaction directly to the audience so that no limitations of distance and time to communicate with each other . One of the local radio located in the city of Pekanbaru is independent FM radio, a radio company that is engaged in the media of course also apply good management such as planning, organizing, implementing up on stage in order to create effective monitoring of performance and quality of the radio. In addition it is no less important part of a radio ad that is on the main source of income from media such as radio, in order to produce quality advertising the main functions of management should also be applied in the production process so that the resulting advertisement competitiveness and accordance with the request of the advertiser. This study aims to determine how the advertising production management conducted by independent radio 98.3 FM Pekanbaru such as production planning, organizing production, production to execution stage production supervision ads.This study uses qualitative descriptive approach. The study is located in a standalone FM radio, streets Tambusai lord no. 07 Pekanbaru with production management research object advertising on independent FM radio and a subject of research is the general manager, program manager, finance, marketing, creative, production, broadcasters and advertisers with some data collection techniques using in-depth observation and interviews and documentation .The results of this study showed Applied management in the production process of advertising done by independent FM radio like a stage production planning, organizing or sharing tasks are handled according to the field, then the implementation of the production process from scripting to the ad and the last stage is a supervisory control of all activities that have been carried out in order to be evaluated in order to create better results than before.Keyword: Managament, Radio, Communication, Mass Media, Advertaising.